2007
DOI: 10.1111/j.1574-6968.2006.00577.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indole-3-butyric acid on phytoplasmas in infected Catharanthus roseus shoots grown in vitro

Abstract: Phytoplasmas are noncultivable bacteria usually maintained in Catharanthus roseus shoots grown in vitro on MS medium with benzylaminopurine. The aim of our research was to examine the influence of indole-3-butyric acid (IBA) on C. roseus shoots infected with three different phytoplasma strains. Supplement of IBA in the medium supported plant growth, photosynthesis and remission of symptoms in all phytoplasma-infected shoots, but had no effect on the presence of EY-C and SA-I phytoplasma strains in tested tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
3
25
0
Order By: Relevance
“…Such growth and developmental abnormalities are suggestive of profound perturbations in plant hormone balance. Phytoplasmal infection also causes impaired amino acid and carbohydrate translocation, and inhibited photosynthesis (Lepka et al 1999;Bertamini et al 2002a, b;Curković-Perica et al 2007). Studies have revealed that phytoplasma infection suppresses auxin signaling and biosynthesis (Hoshi et al 2009).…”
Section: Potential Virulence Factorsmentioning
confidence: 99%
“…Such growth and developmental abnormalities are suggestive of profound perturbations in plant hormone balance. Phytoplasmal infection also causes impaired amino acid and carbohydrate translocation, and inhibited photosynthesis (Lepka et al 1999;Bertamini et al 2002a, b;Curković-Perica et al 2007). Studies have revealed that phytoplasma infection suppresses auxin signaling and biosynthesis (Hoshi et al 2009).…”
Section: Potential Virulence Factorsmentioning
confidence: 99%
“…In infected plants, phytoplasmas colonize sieve cells of phloem tissue and typically induce disease symptoms involving impaired amino acid and carbohydrate translocation, disrupted hormonal balance, and rapid senescence (3)(4)(5)(6)(7). In their natural insect vectors, phytoplasmas traverse the intestinal wall, circulate in hemolymph, and multiply in tissues including salivary glands, where phytoplasma cells are incorporated into saliva injected into plants during inoculation (8).…”
mentioning
confidence: 99%
“…Numbers of reports have revealed that changes in chlorophylls content and photosynthetic performance can be considered as very sensitive indicators for different biotic and abiotic stresses as well as developmental processes in higher plants (MUNNE-BOSCH 2008, TAKAHASHI andMURATA 2008, ]URKOVI]- PERICA et al 2007, FULGOSI et al 2005, PFANNSCHMIDT 2003, MITTLER 2002. Bleaching is often caused by disturbance in mineral nutrition.…”
Section: Discussionmentioning
confidence: 99%